What determines the neutral rate of interest in an emerging economy? - Julio A. Carrillo; Rocio Elizondo; Cid Alonso Rodríguez-Pérez; Jessica Roldán-Pe\~na (Banco de México, 2018)
Evidence suggests that potential growth and the neutral rate co-move in advanced economies. In contrast, this co-movement is not observed in emerging economies. We argue that capital flows may explain this behavior. We focus on Mexico, a benchmark emerging economy, and find that capital inflows may account for a temporary reduction in the Mexican neutral rate after the global financial crisis. These inflows surged during the implementation of unconventional monetary policies in advanced economies. In turn, low-frequency changes in the neutral rate may be attributed to increasing domestic savings, demographics, and a decreasing global long-run real interest rate. These results are largely consistent with other studies showing that the neutral rate has decreased in the last 25 years in advanced and emerging economies.
Keywords: C10; E43; E52; 330; Neutral rate of interest; emerging market economies; transitory and structural factors